PEMANFAATAN E-LEARNING BERBASIS WEBSITE SEBAGAI MEDIA PEMBELAJARAN MAHASISWA STIE INDONESIA MALANG - Jhanua Rizal Idfiano; Nur Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTConventional Accounting systems and used a learning media such as blackboards, notebooks, ledgers, and calculator is a general thing and too boring in Indonesia. In this era, technology is experiencing rapid growth and adaptation for a curriculum and materials can be met best through online learning or can be referred to as e-learning. This study aims to determine how the use of e-learning-based website as a learning media for students STIE Indonesia Malang. This research uses qualitative descriptive and questionnaires as the main data. Analysis of the data in this study using data collection and data reduction after it's done will be continue to presentation of the data and drawing conclusions. The number of respondents in this study were 40 respondents. Results from this study is the use of e-learning-based website as a learning media for students STIE Indonesia Malang is has been used well, the suitability of the material content in e-learning with books and easily to understood, the operating system of e-learning-based website smoothly, value students' increased than before, the creation of a discussion forum so that questions can be answered effectively, and creating learning motivation of the students in learning activities.             Keyword: E-Learning, website, learning media